Study of the Possibilities of Improving Maintenance of Technological Equipment Subject to Wear - Florea, Vlad Alexandru; Ionică, Andreea Cristina; Florea, Adrian; Itu, Răzvan-Bogdan; Popescu-Stelea, Mihai (Processes, 2022)
The rapid development of science and technology, and the restructuring of the mining extraction industry, bring about profound changes in the structure and complexity of technological equipment used in mining. In this paper, the Reliability Centered Maintenance (RCM) method has been applied to analyze the components of the KSW-460NE shearer machine, which fails quite frequently. The cutter drums do not match from a constructive point of view, and the concrete operation conditions, alongside the picks (being in direct contact with coal and hard inclusions) and guides are submitted to intense abrasion wear, showing a great number of failures. The data collected following the machine’s exploitation allowed parameter determination characterizing the reliability of the components mentioned, the manner of failure, and the effects. Using calculation methods, it has been possible to facilitate the interpretation of the result in view of establishing measures required to improve maintenance of the dominant components of the machine, determining replacement intervals, in accordance with an imposed reliability and maintainability. The results of the study assist in the choice of suitable hardening materials for the reconditioning of cutter drums and guides that are necessary for practical trials, by which their operating times, and replacement intervals, respectively, might be additionally improved.